Monetizing housing for retirement in Singapore - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2015)
In 2015, the value of housing assets owned by households in Singapore at the aggregate level was 55% of their net worth.1 Ninety percent of Singapore households owned their homes, meaning that almost all households had wealth saved in housing, and households’ housing wealth was 2.1 times that of the country’s gross domestic product. In addition, Singapore is facing an aging population. The resident old age support ratio, defined as the number of persons aged 20–64 per person aged 65 years and over, decreased from 9.0 in 2000 to 5.7 in 2015.2 Against this backdrop of asset-rich and aging households, an increasingly common trend in East Asia, Singapore is exploring ways to enable homeowners to unlock equity from their homes and improve living standards for elderly households.